Pengujian Komposit Serat Alami - Rizki Romadon Siregar; Yos Nofendri (Prosiding Seminar Nasional Teknoka, 2025)
Over the past two decades, driven by growing awareness of environmental sustainability and the availability of renewable resources, the development of natural fiber-reinforced composites has progressed significantly. This review summarizes recent studies on the mechanical behavior of composites reinforced with bamboo, coconut, and oil palm fibers. The discussion focuses on the effects of chemical treatments on tensile, flexural, and impact strength, based on 24 peer-reviewed articles indexed in Scopus and Google Scholar from 2020 to 2025. Results indicate that alkali treatment using 5–10% NaOH improves tensile strength by up to 40% and flexural strength by 25% compared to untreated composites. Moreover, hybridization of bamboo and oil palm fibers enhances impact energy absorption by approximately 30%. Overall, mechanical performance strongly depends on fiber orientation, volume fraction, and interfacial bonding. This review provides a comprehensive synthesis for developing sustainable composites for future structural and automotive applications.